2017
DOI: 10.1039/c7sm01005b
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of multi-flavored two-dimensional colloidal crystals

Abstract: We systematically investigate the assembly of binary multi-flavored colloidal mixtures in two dimensions. In these mixtures all pairwise interactions between species may be tuned independently. This introduces an additional degree of freedom over more traditional binary mixtures with fixed mixing rules, which is anticipated to open new avenues for directed self-assembly. At present, colloidal self-assembly into non-trivial lattices tends to require either high pressures for isotropically interacting particles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…This sequence of phases is accompanied by a change in the relative stoichiometry from one to zero. These results are consistent with previous computational studies (25,26).…”
Section: Physicssupporting
confidence: 94%
“…This sequence of phases is accompanied by a change in the relative stoichiometry from one to zero. These results are consistent with previous computational studies (25,26).…”
Section: Physicssupporting
confidence: 94%
“…Specifically, we have applied this methodology to probe the self-assembly of monodisperse colloidal monolayers formed from systems inspired by the multi-flavoring motif used in DFP assembly; this scheme enables all pairwise interactions in the system to become independent of one another, qualitatively ranging from being attractive to repulsive. In the limit of strong binding, the ground state ( T * → 0) serves as a reasonable approximation of the thermodynamically stable state 55 . Multi-flavored binary mixtures of colloids dominated by enthalpic interactions are known to exhibit a wide variety of morphologies, both experimentally and theoretically 18,55 ; however, the full impact of stoichiometry on the thermodynamics of their self-assembly is not yet understood.…”
Section: Resultsmentioning
confidence: 99%
“…In the limit of strong binding, the ground state ( T * → 0) serves as a reasonable approximation of the thermodynamically stable state 55 . Multi-flavored binary mixtures of colloids dominated by enthalpic interactions are known to exhibit a wide variety of morphologies, both experimentally and theoretically 18,55 ; however, the full impact of stoichiometry on the thermodynamics of their self-assembly is not yet understood. Here we employ a simplified model (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigation into the self-assembly of two-dimensional multiflavored nanoscale colloids revealed that their morphologies could be rationalized on the basis of energetic arguments. 40 However, three-dimensional micron-scale systems remain largely unexplored systematically. Furthermore, many studies of binary DFP systems focus on cases where size disparity between the system components is used in addition to interparticle interactions to drive the assembly towards desired structures.…”
mentioning
confidence: 99%